C.F. Wells casting polymer from 250-pound autoclave (1938)
Two views of C.F. Wells casting polymer from a 250-pound autoclave during the early stages of nylon production and research at the DuPont Experimental Station in Wilmington, Delaware. During production, a partially-evaporated nylon salt solution was fed into the autoclave and heated to 275 degrees centigrade under a pressure of 275 pounds per square inch in order to precipitate polymerization. Once polymerization occurred, additional water was bled off and the pressure was slowly reduced to atmospheric levels before the polymer was extruded. As visible in the photographs, the hot polymer ribbon was extruded from the bottom of the autoclave into a trough of water to cool. Subsequently, the ribbon was wound onto a reel before being broken into nylon chips for spinning.
Keywords: Employees; Nylon; Polymers; Nylon--Testing; E.I. du Pont de Nemours & Company. Experimental Station; E.I. du Pont de Nemours & Company; Machinery; Autoclaves